Interprofessional collaboration in emergency departments: The importance of teamwork among nurses, pharmacists, medical records, and physicians - Almanna, Mohammad Abdullah; Alanazi, Dhiyaa Manawer; Al Enazi, Sami Mohammed; Alaujan, Badour Subhi; Zamzami, Bander Ahmad; Alanazi, Nadin Lafi; Ababtain, Hind Amer; Altalouhi, Fatmah Malfi; Alenizi, Eman Smair; Aldossary, Ghuzyel Fahad; Alanazi, Nouf Hamed; Alshaibani, Reem Sultan; et al. (International journal of health sciences, 2020)
Background: Interprofessional cooperation (IPC) is becoming more often used but is done in various ways in primary care. Aim of Work – The goal of this study was to evaluate the efficacy of Interprofessional Collaboration (IPC) in primary care settings. Methods: A meta-analysis was conducted to provide a comprehensive evaluation of many systematic reviews. We conducted a comprehensive search across nine databases and used a rigorous double selection and data extraction approach. The patient-related outcomes were classified and the results were recorded as either improvement (+), deterioration (–), mixed results (?), or no change (0). Results: Overall, the use of interprofessional collaboration (IPC) in primary care was advantageous for patients, while the specific benefits varied depending on the kind of IPC used. While evaluations examining the use of interprofessional collaboration (IPC) in primary care, which has a broad range of applications, indicated improved care procedures and increased patient satisfaction, different forms of IPC yielded varied findings in terms of clinical outcomes, healthcare utilization, and patient-reported outcomes. Furthermore, evaluations that specifically examined treatments derived from established and well-defined frameworks, such as collaborative care, often indicated a greater number of advantages.